Recent observed country‐wide climate trends in Morocco. (29th July 2020) - Driouech, Fatima; Stafi, Hafid; Khouakhi, Abdou; Moutia, Sara; Badi, Wafae; ElRhaz, Khalid; Chehbouni, Abdelghani
Abstract: In this study, we evaluate trends in precipitation and temperature and their related extreme indices in Morocco based on a set of National Climate Monitoring Products defined the by the commission for climatology of the WMO. We use daily precipitation, maximum and minimum temperature data from 30 meteorological stations distributed throughout the country and covering the period from 1960 to 2016. Statistically significant increasing trends in warm temperature events and a tendency towards decreasing cold extremes at both daytime and night are depicted across the country consistent with the generalized observed global warming. We found that the daily temperature in Morocco has risen with higher rates than the global scale. The depicted trend of 0.33°C per decade corresponds to a warming of approximately 1.1°C for the period 1984–2016. The annual mean precipitation and the standardized drought index show less spatially consistent tendencies despite the predominance of negative trends. Considering the effect of the warming in the analysis of drought evolution using the Standardized Precipitation‐Evapotranspiration Index, we detected statistically significant trends towards dryer conditions in different regions of the northern half of the country. Analysis of the relationship between precipitation in Morocco and the large‐scale atmospheric circulation in the Atlantic area confirmed the effects of the North Atlantic Oscillation, especially for the winter season (with low influence at the annual scale). Moreover, we found that the NAO exerts significant influence on winter extreme temperatures during night time. However, such correlations alone may not explain the depicted significant generalized warming trends and the drying evolution. Abstract : A tendency towards warmer and dryer conditions in Morocco is detected over the last five decades using observations from 30 meteorological stations distributed across the main climate zones of the country. Observed warming in Morocco is associated with an increase in high temperature extremes and a decrease in cold extremes. Higher number stations with statistically significant trends towards dryer conditions are depicted using the SPEI compared to the SPI, highlighting the combined effect of temperature and precipitation changes. Trends in mean annual temperature anomalies at the country scale in Morocco (left panel). The right panel shows the trends at each individual station.